Postmortem metabolomics: Correlating time‐dependent concentration changes of xenobiotic and endogenous compounds. Issue 8 (1st June 2020) - Brockbals, Lana; Staeheli, Sandra N.; Kraemer, Thomas; Steuer, Andrea E.
Abstract: Postmortem redistribution (PMR) describes the artificial postmortem concentration changes of xenobiotics that may pose major challenges in forensic toxicology. Only a few studies have systematically investigated time‐dependent postmortem drug concentration changes so far and the a posteriori estimation of the occurrence of PMR is not yet possible. In this context, the general concept that postmortem biochemical changes in blood might parallel drug redistribution mechanisms seems promising. Thus, the current study investigated the possible correlations between time‐dependent postmortem concentration changes of xenobiotic and endogenous compounds; exemplified for authentic morphine (n = 19) and methadone (n = 11) cases. Peripheral blood samples at two time‐points postmortem were analyzed for morphine and methadone concentrations and an (un)targeted postmortem metabolomics approach was utilized to combine targeted quantitative analysis of 56 endogenous analytes and untargeted screening for endogenous compounds (characterizing 1174 features); liquid and gas chromatography–mass spectrometry was used respectively. Individual statistically significant correlations between morphine/methadone and endogenous compounds/features could be determined. Hence, the general applicability of the proposed concept could successfully be confirmed. To verify the reproducibility and robustness of the correlating behavior, a larger dataset must be analyzed next. Once a marker/set of markers is found (e.g. robust correlation with specific xenobiotic or xenobiotic class), these could be used as surrogates to further study the time‐dependent PMR in a broader variety of cases (e.g. independent of a xenobiotic drug present). A crucial next step will also be the attempt to create a statistical model that allows a posteriori estimation of PMR occurrence of xenobiotics to assist forensic toxicologists in postmortem case interpretation. Abstract : Individual statistically significant correlations between time‐dependent postmortem concentration changes of morphine/methadone and endogenous compounds were determined. This proof‐of‐concept‐study successfully showed the potential to use postmortem biochemical changes of endogenous metabolites to aim for an a posteriori estimation of the occurrence of postmortem redistribution phenomena once reproducibility and robustness of the correlating behavior is confirmed with a larger dataset.